Literary Tafsīr and Qur’anic Narratives: Muḥammad Aḥmad Khalafullāh and A.H. Johns in Comparative Perspective - Nuzul Fitriansyah (Basmala: Journal of Qur’an and Hadith, 2025)
Literary approaches to Qur’anic narratives are frequently characterized in contemporary scholarship as methodological responses to the predominance of historical-positivist interpretations. Nevertheless, existing research often treats literary tafsīr as a relatively homogeneous paradigm, paying insufficient attention to the epistemological distinctions underlying approaches that appear methodologically analogous. As a result, significant divergences concerning conceptions of revelatory truth, the role of history, and interpretive authority within literary readings of the Qurʾān remain inadequately examined. This lacuna is particularly evident in studies of Muḥammad Aḥmad Khalafullāh and A.H. Johns, who are commonly categorized together as proponents of literary interpretation despite embodying distinct epistemological orientations. This article seeks to address this gap through a critical comparative analysis of Khalafullāh’s literary–historical critique and Johns’ narrative criticism in their interpretations of Qur’anic narratives. Employing qualitative library research and comparative textual analysis, the study scrutinizes their principal works, with particular emphasis on their methodological applications to the stories of the Companions of the Cave and the Prophet Job. The findings demonstrate that a shared rejection of positivist historicism does not yield a unified conception of truth. Khalafullāh locates the truth of Qur’anic narratives in their communicative purpose and moral efficacy, whereas Johns defines truth in terms of narrative coherence shaped by the processes of revelation and reader engagement. This article contends that such epistemological tension constitutes an internal boundary within literary tafsīr itself. The study highlights the necessity for a more epistemologically reflective framework for literary interpretation—one that harmonizes methodological innovation with theological responsibility in contemporary Qur’anic studies. [Pendekatan sastra terhadap kisah-kisah al-Qurʾān kerap diposisikan dalam literatur sebagai respons metodologis terhadap dominasi pembacaan historis-positivistik. Namun, kajian-kajian yang ada cenderung memperlakukan tafsir sastra sebagai kategori yang relatif homogen, tanpa menguji secara kritis perbedaan asumsi epistemologis yang bekerja di balik pendekatan-pendekatan yang secara metodologis tampak serupa. Akibatnya, perbedaan konsepsi tentang kebenaran wahyu, fungsi sejarah, dan otoritas penafsiran dalam tafsir sastra al-Qurʾān sering kali luput dari analisis sistematis. Keterbatasan ini tampak jelas dalam studi terhadap pemikiran Muḥammad Aḥmad Khalafullāh dan A. H. Johns yang, meskipun sama-sama diklasifikasikan sebagai tokoh tafsir sastra, pada dasarnya merepresentasikan orientasi epistemologis yang berbeda. Artikel ini bertujuan untuk mengungkap dan menganalisis perbedaan epistemologis tersebut melalui perbandingan kritis atas pendekatan sastra Khalafullāh dan kritik naratif Johns dalam penafsiran kisah-kisah al-Qurʾān. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka dengan analisis teks komparatif terhadap karya-karya utama kedua tokoh, khususnya dalam penerapan metode mereka pada kisah Aṣḥāb al-Kahf dan Nabi Ayyūb. . Artikel ini berargumen bahwa ketegangan epistemologis tersebut menandai batas internal tafsir sastra al-Qurʾān. Hasil penelitian menunjukkan bahwa penolakan bersama terhadap historisisme positivistik tidak serta-merta menghasilkan paradigma kebenaran yang sama. Khalafullāh memindahkan kebenaran kisah Qurʾān ke ranah tujuan komunikatif dan dampak moral, sementara Johns menegaskan kebenaran melalui koherensi struktural narasi dalam dinamika pewahyuan serta interaksi pembaca dengan teks. Implikasi penelitian ini menegaskan perlunya kerangka tafsir sastra yang lebih reflektif secara epistemologis agar inovasi metodologis tidak berujung pada ambiguitas teologis dalam studi al-Qurʾān kontemporer.]